The role of heat pump in heating decarbonization for China carbon neutrality - Hongzhi Yan; Ruzhu Wang; Zhang, Chuan; Xu, Zhenyuan; Hu, Bin; Zhao Shao (Carbon Neutrality, 2022)
Heating decarbonization is a major challenge for China to meet its 2060 carbon neutral commitment, yet most existing studies on China's carbon neutrality focus on supply side (e.g., grid decarbonization, zero-carbon fuel) rather than demand side (e.g., heating and cooling in buildings and industry). In terms of end use energy consumption, heating and cooling accounts for 50% of the total energy consumption, and heat pumps would be an effective driver for heating decarbonization along with the decarbonization on power generation side. Previous study has discussed the underestimated role of the heat pump in achieving China's goal of carbon neutrality by 2060. In this paper, various investigation and assessments on heat pumps from research to applications are presented. The maximum decarbonization potential from heat pump in a carbon neutral China future could reach around 1532Mton and 670Mton for buildings and industrial heating respectively, which show nearly 2 billion tons CO2 emission reduction, 20% current CO2 emission in China. Moreover, a region-specific technology roadmap for heat pump development in China is suggested. With collaborated efforts from government incentive, technology R&D, and market regulation, heat pump could play a significant role in China's 2060 carbon neutrality.